Frequency of resistance to Vip3Aa20 toxin from Bacillus thuringiensis in Spodoptera frugiperda (Lepidoptera: Noctuidae) populations in Brazil. (October 2015) - Bernardi, Oderlei; Bernardi, Daniel; Ribeiro, Rebeca S.; Okuma, Daniela M.; Salmeron, Eloisa; Fatoretto, Julio; Medeiros, Fernanda C.L.; Burd, Tony; Omoto, Celso
Abstract: High-dose/refuge is the most common resistant management strategy used to delay or prevent pest adaptation to transgenic plants expressing Bacillus thuringiensis Berliner toxins. The success of this strategy depends, among other factors, on a low initial resistance allele frequency. In this study, we used genotypic and phenotypic methods to estimate the frequency of resistance to Vip3Aa20 toxin in Spodoptera frugiperda (J. E. Smith) in Brazil. In genotypic monitoring (F2 screen), 11 populations were screened from 2013 to 2014 in diet-overlay or excised-leaf bioassays. In phenotypic monitoring, 50 populations were screened from 2013 to 2015, by exposition of neonates at a diagnostic concentration of 3600 ng/cm 2 of Vip3Aa20 in diet-overlay bioassay. The resistance allele frequency to Vip3Aa20 overlay on diet or expressed on corn leaves was similar 0.0012 (95% CI, 0–0.0033) and 0.0011 (95% CI, 0–0.0031), with an overall frequency of 0.0009 (95% CI, 0–0.0021). The resistance allele frequency does not differ among populations from different Brazilian states. In the phenotypic monitoring, only three populations MS19, MT24 and PR51 from Chapadão do Sul (MS), Lucas do Rio Verde (MT) and Castro (PR) showed larval survival ranging from 0.87 to 0.97%, differing from a susceptible reference population. In summary, the frequency of resistance to Vip3Aa20 toxin in Brazilian populations of S. frugiperda was low. Therefore, if other factors such as recessive inheritance of resistance and high level of refuge compliance are met, the risk of resistance to Vip3Aa20 in S. frugiperda populations in Brazil can be minimized. Highlights: We conducted resistance risk assessment of Spodoptera frugiperda to Vip3Aa20. We used genotypic and phenotypic screens to estimate Vip3Aa20 resistance allele frequencies. A total of 852 two-parent families derived from 11 field-collected populations were screened. Susceptibility monitoring at a diagnostic concentration was conducted in 50 field populations. The frequency of alleles for resistance to Vip3Aa20 toxin in S. frugiperda was low.